Biomechanical comparisons of F.E.R.I. techniques with different type of intramedullary screws fixation for Jones fractures - Su, Kuo-Chih; Yen, Yu-Chun; Wang, Chun-Hsiang; Wang, Yi-Lun; Wang, Shun-Ping (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Jones fractures frequently fail to unite, and adequate fixation stability is crucial. This study aimed to elucidate the biomechanical stability of various intramedullary screw fixation constructs. Methods: Jones fracture model over the proximal 5th metatarsal of artificial bone was created in all specimens. Six groups were divided based on varied screw constructs with different screw lengths, either 30 or 40 mm, including cannulated screws—C30 and C40 groups, one high-resistance suture combined with intramedullary cannulated screws (F.E.R.I. technique)—CF30 and CF40 groups, and second-generation headless compression screws (SG-HCS) —HL30 and HL40 groups. Mechanical testing was conducted sequentially, and the maximal force (N) and stiffness (N/mm) of all constructs were recorded. Results: The maximal force (N) at 1.0 mm downward displacement in C30, C40, CF30, CF40, HL30, and HL40 groups were 0.56 ± 0.02, 0.49 ± 0.02, 0.65 ± 0.02, 0.49 ± 0.01, 0.68 ± 0.02, and 0.73 ± 0.02, respectively, and the stiffness (N/mm) in subgroups were 0.49 ± 0.01, 0.43 ± 0.01, 0.67 ± 0.01, 0.42 ± 0.01, 0.61 ± 0.01, and 0.58 ± 0.02, respectively. SG-HCS subgroups exhibited greater maximal force and stiffness than conventional cannulated screws. Screws of 30 mm in length demonstrated better stability than all 40 mm-length screws in each subgroup. In C30 fixation, the stiffness and maximum force endured increased by 1.16 and 1.12 times, respectively, compared with the C40 fixation method. There were no significant differences between CF30 and SG-HCS groups. Only the F.E.R.I technique combined with the 4.5 mm cannulated screw of 30 mm in length increased the biomechanical stability for Jones fractures. Discussion: These biomechanical findings help clinicians decide on better screw fixation options for greater stability in Jones fractures, especially when large-diameter screws are limited in use. However, this biomechanical testing of intramedullary screw fixation on Jones fracture model lacks clinical validation and no comparisons to extramedullary plate fixations. Moving forward, additional clinical and biomechanical research is necessary to validate our findings.